A continuous income-based grade gap decomposition on university course grades. Issue 31 (3rd July 2018) - Ulrick, Shawn W.; Mongeon, Kevin P.; Giannetto, Michael P.
ABSTRACT: The earnings premium for education, and higher education in particular, is well documented. This article examines the college achievement gap between students coming from positions of high and low socio-economic status. Other papers have also looked at this issue, often by employing, at least in part, an Oaxaca decomposition. Past papers artificially divided socio-economic status into binary groups of high and low, in order to employ the decomposition. Socio-economic status is innately a continuous variable. Therefore, we implement a continuous version of the Oaxaca decomposition. Higher socio-economic students are both slightly better prepared in terms of observable characteristics and have better returns to their characteristics than lower socio-economic students. Notable differences across results obtained from the binary and continuous decomposition methods are discussed.